The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20020953
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Backward Walking Performance in Parkinson’s Disease with and without Freezing of Gait—A Systematic Review

Abstract: Introduction: Parkinson’s disease (PD) is a neurodegenerative disease characterized by motor symptoms and gait impairments. Among them, freezing of gait (FOG) is one of the most disabling manifestations. Backward walking (BW) is an activity of daily life that individuals with PD might find difficult and could cause falls. Recent studies have reported that gait impairments in PD were more pronounced in BW, particularly in people presenting FOG. However, to the best of our knowledge, no systematic review has syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Given the fundamental importance of walking in everyday activities and its tight connection with well-being, gait training is frequently part of the rehabilitation protocols. Forward Walking (FW) can easily be performed by individuals of all ages and fitness levels, and it is commonly indicated for patients recovering from injuries and surgeries at the lower limbs, suffering from chronic conditions, disabilities and neurodegenerative disorders [ 13 ]. More specifically, walking helps preserving muscular strength and balance control, coordination and proprioception, which can reduce the risk of falls and injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fundamental importance of walking in everyday activities and its tight connection with well-being, gait training is frequently part of the rehabilitation protocols. Forward Walking (FW) can easily be performed by individuals of all ages and fitness levels, and it is commonly indicated for patients recovering from injuries and surgeries at the lower limbs, suffering from chronic conditions, disabilities and neurodegenerative disorders [ 13 ]. More specifically, walking helps preserving muscular strength and balance control, coordination and proprioception, which can reduce the risk of falls and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 19 ] dedicated attention to the knee external abduction moment during BW, pointing out that this motor task reduced the joint loading and confirmed its potentiality in the management of knee osteoarthritis. Milane et al [ 13 ] showed that BW challenges the body differently than FW, stimulating balance and coordination in a more demanding way, and improving cognitive function, proprioception and spatial awareness. Dissimilarities between FW and BW kinematics have been also identified in people with intellectual disabilities by Gimunova et al [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the occurrence of FOG is highly variable, making it difficult to measure the frequency and duration of FOG attacks. However, FOG patients often exhibit lower gait speed, shorter stride length, worse gait cycle index, and greater gait variability 20‐22 . Therefore, we used objective quantification of gait kinematics in this study to distinguish the gait characteristics of FOG and quantify the treatment efficacy on FOG.…”
mentioning
confidence: 99%